Strategi Pemerintah Kota Dalam Pengembangan Kawasan Wisata Terpadu (KWT): Sebuah Implikasi Intervensi Kebijakan Pengembangan Pariwisata - Rini Zumaida; Hendri Koeswara; Desna Aromatica (Jurnal Administrasi dan Kebijakan Publik, 2022)
The research is a city government policy intervention in the form of a tourism development strategy in the Padang City Integrated Tourism Area. The strategic initiative carried out by the Government of the City of Padang by making a tourist destination an Integrated Tourism Area has changed the face of the City of Padang which is increasingly oriented towards becoming a tourist destination that can improve the economic welfare of the community. The necessity that is carried out by the Padang City Government is to design and develop a strategy to develop an Integrated Tourism Area (KWT). This study used a qualitative approach by elaborating primary and secondary data where the selection of informants was carried out purposively. The strategy used by the Municipal Government of Padang is through organizational strategy, program strategy, resource support strategy, and institutional strategy. The results of the study show that all of these strategies are carried out massively and show the relationship between policy interventions that effectively influence the governance of tourism development. And, this tourism policy intervention has implications for increasing the number of domestic and foreign tourists which also has implications for increasing local revenue (PAD)